The full range of ophthalmological clinical manifestations in systemic lupus erythematosus - Kedia, Nikita; Theillac, Vincent; Paez-Escamilla, Manuel; Indermill, Chad; Gallagher, Denise S.; Adam, Raphaël; Qu-Knafo, Anne Lise; Amari, Fatima; Bottin, Caroline; Chotard, Géraldine; Caillaux, Violaine; Strého, Maté; et al. (Frontiers in Ophthalmology, 2023)
Purpose: To determine the full range of ophthalmologic clinical manifestations in systemic lupus erythematosus (SLE) and to compare the systemic features associated with them. Methods: Files of 13 patients with ocular SLE (n=20 eyes) diagnosed as per the American College of Rheumatology (ACR) 2012 revised criteria were retrospectively reviewed. Results: The following clinical manifestations were found: keratoconjunctivitis sicca (N=3 patients), anterior uveitis associated with an inflammatory pseudo-tumor orbital mass (N=1 patient, 1 eye), episcleritis and periorbital edema (N=1 patient, 2 eyes), posterior scleritis (N=1 patient, 2 eyes), bilateral papillary edema in the context of idiopathic intracranial hypertension (N=1 patient, 1 eye), inflammatory optic neuritis (N=1 patient, 1 eye), and lupus retinopathies with varying degrees of capillary occlusions mainly arteriolar (N=7 patients, 13 eyes) and larger arteries or veins (retinal arteries occlusions and retinal veins occlusions) (N=1 patient, 2 eyes). Some patients presented with combined ophthalmological manifestations. Systemic SLE was discovered by its ophthalmic manifestation in three cases (23%) and was previously known in the other ten cases (77%). On average, ocular symptoms were seen eight years after the initial diagnosis of SLE. Other systemic SLE disorders included cutaneous (77%), joint (38%), central nervous system involvement (CNS) (23%), renal involvement (38%), and oral ulcers (23%). Treatment of the ophthalmic system manifestations of lupus included local steroids therapies along with systemic immunosuppression. The most common laboratory ARC criteria were: high antinuclear antibodies (ANA) (100%), positive anti-Sm (64%), anti-dsDNA (27%), low complement (27%) and positive antiphospholipid (APL) antibodies (18%). Discussion: SLE activity in the ophthalmic system is characterized by its functional severity and the range of involvement can be categorized by anatomical involvement: presence of anterior uveitis, episcleritis, scleritis, periorbital edema, presence of posterior uveitis with retinal vascular ischemia, or papillary edema. Not currently part of the diagnosis criteria of the SLE ACR given its rarity, the ocular localization of the pathology led to the diagnosis of SLE in three cases, thus developing a greater understanding of ocular lupus may help in identifying and treating systemic manifestations of lupus earlier.